Optimization of stability indicating RP-HPLC method for the estimation of an anti-cancer drug Sorafenib Tosylate in pure and pharmaceutical dosage form - Ramesh Jayaprakash; Senthil Kumar Natesan (International Journal of Pharmacy and Analytical Research, 2022)
A simple, specific and precise stability indicating RP- HPLC method has been developed and validated for the estimation of sorafenib tosylate in tablet dosage from using Phenomenex Luna- C18 column (4.5 x 250 mm; 5 µm particle size) as a stationary phase, methanol: acetonitrile: water (65:25: 10 v/v/v) as a mobile phase, flow rate of 1 mL/min and detection was carried out at 248 nm. The retention time of sorafenib was 2.887 minute. RP - HPLC method was developed with linearity range of 20-120 µg/mL of sorafenib tosylate. The correlation coefficient was found to be 0.9997 for sorafenib tosylate. The assay results obtained in good agreement with the corresponding labeled amount by developed method within range of 99.15% - 101.58%. Accuracy, precision, LOD, LOQ, specificity, robustness and ruggedness were met all the acceptance criteria for the validation of analytical method as per ICH Q2 (R1) guideline. This method can be conveniently used to detect the possible degradation product in the dosage form of sorafenib tosylate during stability studies (acidic, alkaline, oxidative, thermal and photolytic). The method proved to be effective on application to a stressed marketed tablet formulation.